Nutritional Value of White Button Mushroom (Agaricus bisporus) Which is Most Widely Consumed in Kurdistan Region-Iraq - Nadir, Hawrez Ali; Al-Zubaidy, Adel Mohan Aday; Al-Rawi, Areej A. Farman; Ibrahim, Kocher Jamal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
This study was conducted in 2018, at Technical College of Applied Sciences, Sulaimani Polytechnic University, Kurdistan Region-Iraq. The aim of the study was to determinate nutritional compositions and some elemental contents in marketable white button mushroom (Agaricus bisporus) that is collected in local markets of Kurdistan Region-Iraq. Five different samples (A: Penjwen product fresh, B: Sulaimani product fresh, C: American caned, D: Valencia Netherlandcaned and E: Erbil product fresh) were collected to be observed. The elements were analyzed by Atomic Absorption Spectrometry methods, and their chemical compassions were determined, too. The collected data were analyzed by One Way ANOVA. The highest fat, protein, fiber and dry matter were obtained from treatment B (3.93%, 43.693%, 15.8% and 10.611%) respectively, and the highest carbohydrate and moisture were found from treatment D (49.267% and 95.053%). The maximum percentage of ash was taken from E (14.11%). Moreover, the highest metabolizable energy was taken from treatment D (296.105 kcal %) and the lowest was taken from parameter E (223.097 kcal %). The highest mineral contents (Zn:15, Mn:1.1, Cu:3.5, Ni:1, Ca:6.7 and Mg:90 ppm) from B, (Fe:15 ppm) from C, (Si:350ppm) from A, and (Na:1080 ppm) from D were taken. However, the lowest elemental contents (Fe:6, Mn:0.48, Ni:0.6, Na:180 and Ca:3.5 ppm) from E, (Zn:5, Cu:0.9 and Mg:35 ppm) from D and B (Si:120 ppm) were taken. Therefore, we recommend carrying out more studies on micronutrients for different marketable crops and consuming fresh mushroom instead of caned mushrooms.